The Pursuit- Next Generation of Hide and Seek with Augmented Reality - Benett, Christoffer; Buchholz, Andrea; Davidsson, Cenny; Tran, Michel (My University, 2015)
As technology has rapidly been integrated in the lives of most people, especially young people, there is a great need to break the pattern of a sedentary lifestyle among this group. While the older generations spent their free time during their youth playing outside, the youth today instead spend their time in front of screens. With this project, our hope is to get people more active by creating a mobile application that integrates a hide and seek type of game with movement in real life. The goal is to find out whether this type of application is a fun way to be active. The application is available for smartphones with either Android or iOS as operating system. The mobile application complements actions of the players during the game, such as navigation on a map as well as setting specific rules for the game, such as the duration of the game. When testing the application, all test subjects found the game to be interesting although the specific game concept needs some further work. All test subjects did however want more games with the same type of interaction on the current market.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science